Undeclared Economic Activity in Central and Eastern Europe : How Taxes Contribute and How Countries Respond to the Problem - Leibfritz, Willi (2012)
The paper examines the incentives and distortions created by tax policy and administration structures that motivate individuals to undeclare or under-declare work in the new EU member countries. It analyses the tax level and the tax structure "mix" of tax instruments, the special taxation regimes set up to attract workers and entrepreneurs back into the formal economy and how tax policies such as the introduction of a "flat tax" on income from labor and capital impacted workers and entrepreneurs in terms of formalizing work. It also attempts to gain some insight into the effectiveness of tax administration by comparing some input and output measures As non-tax factors can amplify the adverse effects of taxes on the labor market and reduce the effectiveness of tax reform, some of these other economic framework conditions are also discussed. This paper concludes by refining the main results and possible best practices for tackling undeclared work. The paper argues that the new EU member countries have had mixed success tackling undeclared work. While taxation matters, other underlying conditions for formal sector activity are also important. Addressing the problem of undeclared work therefore requires a broad policy approach with further improvements in tax policies, tax administration, and in general economic framework conditions for formal sector activity.